2015
DOI: 10.1111/jar.12191
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of People with Intellectual and Developmental Disabilities from SelectUSState Disability Service Systems and Medical Claims Data

Abstract: Age at death remains lower and mortality rates higher for people with intellectual and developmental disabilities. Improved case finding (e.g. medical claims) could provide more complete mortality patterns for the population with intellectual and developmental disabilities to inform the range of access and receipt of supportive and health-related interventions and preventive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 24 publications
7
99
0
Order By: Relevance
“…Gender differences that may have an impact on mortality within the population with ID are not well understood. 124 In our study we observed higher age-and gender-adjusted mortality rates for women (139.5 per 10,000 persons per year) than for men (127.3), although no statistical difference remained when we adjusted for differences in comorbidity between the genders. This was similar to a recent US study 124 utilising information from four state level-disability service systems, which found higher mortality rates for women with ID than for men with ID (18.9 vs. 16.2 per 1000).…”
Section: Mortalitymentioning
confidence: 51%
See 2 more Smart Citations
“…Gender differences that may have an impact on mortality within the population with ID are not well understood. 124 In our study we observed higher age-and gender-adjusted mortality rates for women (139.5 per 10,000 persons per year) than for men (127.3), although no statistical difference remained when we adjusted for differences in comorbidity between the genders. This was similar to a recent US study 124 utilising information from four state level-disability service systems, which found higher mortality rates for women with ID than for men with ID (18.9 vs. 16.2 per 1000).…”
Section: Mortalitymentioning
confidence: 51%
“…124 In our study we observed higher age-and gender-adjusted mortality rates for women (139.5 per 10,000 persons per year) than for men (127.3), although no statistical difference remained when we adjusted for differences in comorbidity between the genders. This was similar to a recent US study 124 utilising information from four state level-disability service systems, which found higher mortality rates for women with ID than for men with ID (18.9 vs. 16.2 per 1000). However, simply comparing overall mortality rates could hide any potential gender disparity, as men of a similar age in the general population may have a higher underlying mortality rate than women from being more likely to engage in higher-risk lifestyles or behaviours, a difference that may not exist within the population with ID.…”
Section: Mortalitymentioning
confidence: 51%
See 1 more Smart Citation
“…There is a growing body of evidence that people with intellectual disability (ID) are at risk of health care disparities, unmet medical needs, and reduced life expectancy compared to the general population (Anderson et al, 2013; Krahn and Fox, 2014; Fenton et al, 2003; Hayden et al, 2005; Kancherla et al, 2013; Morgan et al, 2012; Salvador-Carulla and Symonds, 2016; Heslop and Glover, 2015; Lauer and McCallion, 2015). Recent reports by the United States Public Health Service and the Institute of Medicine identify a number of potential explanations for health disparities for individuals with ID, such as poor access to primary care, failure to include people with ID in public health programs and prevention activities, and insufficient education of health care providers (Krahn and Fox, 2014; Hayden et al, 2005; U.S.…”
Section: Introductionmentioning
confidence: 99%
“…2 Children with ID have an increased risk of early death compared to the general population. 3 In California, for example, children with severe or profound ID have a mortality rate of 3.8 per 1000 deaths, compared to 0.31 per 1000 among all children. 4,5 Survival is further reduced when children with ID suffer from significant motor dysfunction (e.g., epilepsy), progressive congenital conditions (e.g., Down Syndrome), and comorbidities.…”
mentioning
confidence: 99%